SURGICAL OUTCOME OF MUSCLE TRANSPLANTATION AS A MONOCULAR SURGERY FOR LARGE ANGLE STRABISMUS - Puspita, Ika; Patong, Rani Yunita; Marlyanti Nur Rahmah; Maharani, Ratih Natasha (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2023)
Introduction: The management of large-angle strabismus can be difficult for surgeons, and successful outcomes may require multiple surgeries. However, modern surgical techniques aim to achieve desired results with a single operation. Muscle transplantation is one such technique that increases the effective muscle length, allowing for a large correction in a one-stage surgery. Objective: To report the outcome of muscle transplantation surgery in large-angle strabismus. Case Illustration: Three patients presented with large-angle strabismus, of which two cases showed >50∆ ET and one case had >50∆XT. All patients had normal anterior and posterior segment findings and underwent muscle transplantation under general anaesthesia. The first and second cases showed good alignment post-surgery, with no limitations in ocular motility in all gaze directions and improved visual acuity. However, none of the cases achieved stereoscopic vision due to chronic strabismus. In the third case, improvement in the primary position was observed two weeks post-operative, but ocular motility still had limitations. Conclusion: Muscle transplantation is a good option to correct large-angle strabismus, specifically in the unilateral case in a single procedure.